Gastric Cancer Mortality in Ceará in Brazil’s Northeastern, 2000-2022: Spatio- Temporal Study - Lucia Libanez Bessa Campelo Braga; Helio De Almeida Nobre Junior; Jorg Heukelbach; Anderson Fuentes Ferreira; Ana Suzete Lopes; Edson Luiz de Oliveira; Vitor de Sousa Tomé; Taynara Lais Silva; Daniele Calheiros Campelo Maia; Alberto Novaes Ramos Júnior (Revista Brasileira de Cancerologia)
Introduction: In recent decades, the prevalence of gastric cancer (GC) has increased in Brazil’s Northeastern, especially in the state of Ceará. Objective: To analyze temporal trends and spatial patterns of GC mortality over a 23-year period in Ceará. Method: All registered death certificates (DC) (GC registered as any cause of death) from 2000 to 2022 were included. Temporal trends were assessed by joinpoint regression models, while spatial patterns were assessed by spatial autocorrelation, using the local Moran index based on Local Indicators of Spatial Association (LISA). Results: GC was detected in 16,670 DCs (1.5% of all deaths). Age- and sex-adjusted mortality was 8.44/100,000 population. The highest mortality rates were found in the southern parts of the state and around a northern major urban center. Analysis over time showed a rising trend (Average Annual Percent Change: AAPC 1.2; 95%CI 0.6;2.1), especially in males (AAPC 1.6; 95%CI 1.1;2.1), individuals <45 years (AAPC 2.1;3.7), residents of the central region (AAPC 3.2, 95%CI 1.8;5.1) and high deprivation index municipalities (AAPC 2.6, 95%CI 1.3;5.0). Spatial-temporal clusters of high risk for GC-related mortality from 2000 to 2017 were identified, with no statistical significance in the period 2018-2022: clusters were identified in the south until 2011 and in the northwest from 2006 to 2017. Conclusion: GC mortality has increased in Ceará during the study period. High risk areas for GC mortality were identified, enabling focused integrated actions to strengthen prevention, diagnosis, surveillance and control networks.